1988
DOI: 10.1093/ehj/9.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Improved diagnostic value of echocardiography in patients with infective endocarditis by transoesophageal approach. A prospective study

Abstract: In a prospective study, the clinical value of transoesophageal two-dimensional echocardiography (TOE) as compared with transthoracic two-dimensional echocardiography (TTE) was determined in patients with suspected infective endocarditis. Ninety-six patients were studied consecutively with an electronic sector scanner using 2.25 and 3.5 MHz probes for TTE and a 3.5 MHz probe embedded in tip of a flexible 12 mm gastroscope for TOE. Results of surgery and autopsy were available for 20 of the 96 patients with infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
113
0
12

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(130 citation statements)
references
References 0 publications
2
113
0
12
Order By: Relevance
“…23 Another prospective TEE study, however, found no clear correlation of vegetation size with embolization. 95 Overall, these data are compatible with previous observations that in general, mitral vegetations, regardless of size, are associated with higher rates of embolization (25%) than aortic vegetations (10%). Of interest, the highest embolic rate (37%) has been seen in the subset of patients with mitral vegetations attached to the anterior rather than the posterior mitral leaflet.…”
Section: Risk Of Embolizationsupporting
confidence: 91%
See 1 more Smart Citation
“…23 Another prospective TEE study, however, found no clear correlation of vegetation size with embolization. 95 Overall, these data are compatible with previous observations that in general, mitral vegetations, regardless of size, are associated with higher rates of embolization (25%) than aortic vegetations (10%). Of interest, the highest embolic rate (37%) has been seen in the subset of patients with mitral vegetations attached to the anterior rather than the posterior mitral leaflet.…”
Section: Risk Of Embolizationsupporting
confidence: 91%
“…The number of vegetations, the number of valves involved, and vegetation characteristics (eg, lack of calcification) predicted embolic complications in one study. 95 Vegetation mobility has not been shown to be an independent risk factor for embolic events, probably because it is strongly correlated with vegetation size. 23 Embolic events do appear to be predicted by an increase in vegetation size by TEE over 4 to 8 weeks of therapy.…”
Section: Risk Of Embolizationmentioning
confidence: 99%
“…[4][5][6] The sensitivity of TTE varies from 40-63%, and for TEE between 90-100%, while the specificity for both is greater than 95%. [14][15][16] The diagnostic yield of echocardiography reported by Chaudhury et al (64%) was lower, probably due to lack of TEE at that time. 6 The culture positivity of 83.8% of IE in our study is higher than that reported by Math (41%), Chaudhury et al (47%) and Garg et al (67.6%).…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, the current European Society of Cardiology and American Heart Association guidelines (3,9) recommend that any patients suspected of having native valve endocarditis by clinical criteria should be screened by TTE. Furthermore, TTE is rapid and noninvasive, and has excellent specificity for vegetations (4,10). TTE is therefore widely used in IE surveillance.…”
Section: Discussionmentioning
confidence: 99%